N-Glycosylation affects endoplasmic reticulum degradation of a mutated derivative of carboxypeptidase yscY in yeast - Knop, Michael; Hauser, Nicole; Wolf, Dieter H. (Yeast, 1996)
The endoplasmic reticulum (ER) of eukaryotic cells contains a quality control system, that is required for the proteolytic removal of aberrantly folded proteins that accumulate in this organelle. We used genetic and biochemical methods to analyse the involvement of N-glycosylation in the degradation of a mutant derivative of carboxypeptidase yscY in the ER of the yeast Saccharomyces cerevisiae. Our results demonstrate that N-glycosylation of this protein is required for its degradation since an unglycosylated species is retained stably in the ER. Cells that were devoid of the ER-processing alpha 1,2-mannosidase showed reduced degradation of the glycosylated substrate protein. Disruption of CNE1, a gene encoding a putative yeast homologue for calnexin, did not exhibit any effects on the degradation of this substrate protein in vivo. Also, the alpha 1,2-mannosidase-dependent reduction in the degradation rate did not show any correlation with the function of the CNE1 gene product. Our results suggest that the ER of yeast contains a glycosylation-dependent quality control system, as has been shown for higher eukaryotic cells.
Gesehen am 31.08.2017
DOI funktioniert nicht, 31.08.2017